2012
DOI: 10.1097/shk.0b013e318254d41a
|View full text |Cite
|
Sign up to set email alerts
|

Normal-Range Blood Lactate Concentration in Septic Shock Is Prognostic and Predictive

Abstract: We hypothesized that lactate levels even within the normal range are prognostic and that low lactate levels predict a beneficial response to vasopressin infusion in septic shock. We conducted a retrospective analysis using the Vasopressin in Septic Shock Trial (VASST) as a derivation cohort (n = 665), then validated using another single-center septic shock cohort, St Paul's Hospital (SPH) cohort (n = 469). Lactate levels were divided into quartiles. The primary outcome variable was 28-day mortality in both coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
121
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(137 citation statements)
references
References 30 publications
12
121
1
3
Order By: Relevance
“…A handful of smaller studies evaluated patients with sepsis with intermediate lactate values and reported similar findings (15,16,18,(28)(29)(30). In our large, modern cohort, we confirm that rising index lactate values were associated with increased mortality.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…A handful of smaller studies evaluated patients with sepsis with intermediate lactate values and reported similar findings (15,16,18,(28)(29)(30). In our large, modern cohort, we confirm that rising index lactate values were associated with increased mortality.…”
Section: Discussionsupporting
confidence: 74%
“…In a cohort of 5,041 critically ill patients, Nichol and colleagues (35) found that the addition of dynamic lactate indices to existing severity measures dramatically improved outcomes prediction. In this context, the current study confirms a consistent relationship between lactate indices and mortality across a broad population of patients with sepsis that is stratified by, but independent of, shock or the need for critical care (16,28,30,35,37).…”
Section: Discussionsupporting
confidence: 57%
“…The SV then is measured beat by beat, using a pulse contour analysis, through a thermistor tipped catheter inserted into a peripheral artery. The SV, CI, and CO measured by the two types of calibrated pulse contour technologies were shown to agree well with the values obtained with PAC [19][20]. Moreover, TPTD itself offers other critical volumetric parameters (GEDV, ITBV) and organ function parameters (EVLW, PVPi, and CPO).…”
Section: How Do the Parameters Provided By Hemodynamic Monitoring Helsupporting
confidence: 69%
“…The new ESICMc-2014 report underlines the fact that blood lactate levels > 2mEq/L should be considered the hallmark of an existing shock syndrome [2,20]. Also, previous trials showed that the concomitant presence of hemodynamic shock plus hyperlactatemia> 4.0 mmol/L is associated with a mortality of 30% to 45% [12.19].…”
Section: Metabolic Markers Of Regional and Microcirculation And The Amentioning
confidence: 99%
“…Lactic acidosis is frequently associated with multiple organ failure, which has an extremely poor survival rate (18). Because the outcome of multiple organ failure treatment is closely correlated with blood lactate levels (19)(20)(21)(22), it is believed that reducing blood lactate levels would improve outcomes in this setting. To test whether pharmacological PHD2 inhibition could have a beneficial effect on such severe medical conditions, including endotoxin-induced shock, wild-type mice were treated with vehicle or the PHD inhibitor GSK360A by oral gavage immediately after the i.p.…”
Section: Phd2-lko (N=7)mentioning
confidence: 99%